Employing authentic resources in boosting verbal competence of language learners - Sultonqulov , G’ayratjon (The Lingua Spectrum, 2025)
This article sheds light upon the application of authentic materials – such as real-world texts, audio recordings, and movies – in developing the speaking skills of learners. It recounts several advantages of using these materials, including increased engagement, exposure to natural language use, and the fostering critical thinking skills. Authentic resources provide higher and lower-level learners with contextually relevant vocabulary and structures, encouraging a deeper understanding of language in practical settings. The article also addresses potential disadvantages, such as the difficulty of selecting appropriate materials that match learners' proficiency levels and the risk of overwhelming students with complex language. Additionally, it highlights the need for careful guidance and support from educators to ensure that learners can effectively navigate and benefit from authentic resources. Alongside, this article explores the benefits of using authentic articles for ESP students and offers practical strategies for implementation. English for Specific Purposes (ESP) is a tailored approach to language education that focuses on the specific needs of learners based on their professional or academic contexts. One of the most effective ways to enhance speaking skills in ESP students is through the use of authentic articles. These resources provide real-world language exposure, relevant vocabulary, and contextualized learning opportunities that can significantly improve students' speaking abilities. Overall, the article presents a balanced view on the integration of authentic materials in language education, emphasizing their potential to significantly boost verbal competence while acknowledging the challenges that may arise in their implementation.